Hela keta and educational leadership in East Nusa Tenggara: an analysis of cultural practices - Heryon Bernard Mbuik; Hingrida Margarita Anastasia Hendrik (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Educational leadership in many schools in East Nusa Tenggara, Indonesia, is often dominated by bureaucratic and hierarchical decision-making that limits teacher participation and school community collaboration. This study aims to analyze the core values of Hela Keta and develop a culturally based educational leadership model in the Timor context. A qualitative descriptive approach with a simple ethnographic design was employed. Data were collected through participatory observation, in-depth interviews with traditional leaders, principals, and teachers, and document analysis in Timor Tengah Selatan and Kupang. Participants were selected purposively to represent key stakeholders in school leadership and local cultural practices. Data were analyzed thematically through coding, categorization, and triangulation. Findings reveal that Hela Keta embodies values of reciprocity, solidarity, deliberation, and collective responsibility, shaping both symbolic and practical leadership. These values manifest in participatory decision-making, school community collaboration, and a value-based school culture. Based on these findings, a Hela Keta-based educational leadership model is proposed, offering a culturally responsive and values-oriented framework for school leadership. The model provides guidance for principals and policymakers in implementing leadership practices that respect local cultural norms while strengthening school governance. Future research can explore the application of this model in other culturally diverse educational settings to enhance its relevance and adaptability.